Coordinated Modulation of Energy Metabolism and Inflammation by Branched-Chain Amino Acids and Fatty Acids - Ye, Zhenhong; Wang, Siyu; Zhang, Chunmei; Zhao, Yue (Frontiers in Endocrinology, 2020)
As important metabolic substrates, branched-chain amino acids (BCAA) and fatty acids (FAs) are able to participate in many significant physiological processes, such as mitochondrial biogenesis, energy metabolism, and inflammation, along with intermediate metabolites generated in their catabolism. The increased levels of BCAA and fatty acids can lead to mitochondrial dysfunction by reducing mitochondrial biogenesis and adenosine triphosphate (ATP) production and interfering with glycolysis, oxidative phosphorylation, the tricarboxylic acid cycle (TCA) cycle, and fatty acid oxidation. BCAA can directly activate the mammalian target of rapamycin (mTOR) signaling pathway to induce insulin resistance, or function together with fatty acids. In addition, elevated levels of BCAA and fatty acids can activate the canonical nuclear factor-κB (NF-κB) signaling pathway and inflammasome, and regulate mitochondrial dysfunction and metabolic disorders through upregulated inflammatory signals. This review will focus on the mechanisms through which BCAA and fatty acids modulate energy metabolism and inflammation synergistically, and may contribute to discovering new targets for the treatment of metabolic diseases.